EFFECTIVENESS OF EARLY DETECTION OF MALNUTRITION IN CHILDREN AGED 6-29 MONTHS USING ANDROID-BASED APPLICATION - Aro`fah, Suhaela -; Budiman, Selamat (STIKES Suaka Insan, 2023)
Malnutrition is one of the leading health problems of international concern, especially in developing countries. In general, malnutrition is divided into undernutrition and overnutrition, commonly referred to as undernutrition and overnutrition. In Jambi province, malnutrition in children under five still needs attention. To make it easier to detect early on the nutritional status of children aged 6-59 months regularly, an Android-based application modification that can be downloaded through the play store under the name